2022
DOI: 10.3390/healthcare10040714
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Behavioral Effects of the COVID-19 Pandemic on Children and Adolescents with Autism and Their Families: Overview of the Literature and Initial Data from a Multinational Online Survey

Abstract: Since COVID-19 has become a pandemic, everyday life has seen dramatic changes affecting individuals, families, and children with and without autism. Among other things, these changes entail more time at home, digital forms of communication, school closures, and reduced support and intervention. Here, we assess the effects of the pandemic on quality of life for school-age autistic and neurotypical children and adolescents. First, we provide a comprehensive review of the current relevant literature. Next, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 140 publications
0
13
0
1
Order By: Relevance
“…Previous studies of the potential effects of pandemic on the psychological well-being of adolescents with ASD are contradictory, as it shows both negative and positive impacts of the pandemic on the psychological well-being of people with ASD [ 33 , 42 , 43 , 44 , 45 , 46 , 47 ]. Studies conducted in many countries have indicated the significant changes that occurred in the functioning of many people with ASD during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of the potential effects of pandemic on the psychological well-being of adolescents with ASD are contradictory, as it shows both negative and positive impacts of the pandemic on the psychological well-being of people with ASD [ 33 , 42 , 43 , 44 , 45 , 46 , 47 ]. Studies conducted in many countries have indicated the significant changes that occurred in the functioning of many people with ASD during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Maybe the most striking result of the present study is the pronounced increase in the rate of admissions of patients with ASD to our clinics. This nding, which was also shown in other countries, is in contrast with the opinions that children with ASD already are spending their lives at home with their strict routines and have a very limited number of people in social contact; and pandemic might not affect them as much as children with other diagnoses like ADHD which have signi cant bonds with society [10,11]. Since the early days of the pandemic, we had phone calls from families, reporting their children with ASD were more irritable, having more frequent repetitive behaviors, having di culties to get to sleep, and in some kids, less interest in verbal and non-verbal communication.…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, many individuals with SEND have been shielded due to the increased risk of infections and severe forms of COVID-19 ( 41 ). As a result, these individuals' access to the support provided by schools and other help and rehabilitation services has been largely restricted, leading to increased depression and anxiety and worsening of problematic behaviors ( 42 , 43 ). One of the important factors explaining this effect is the loss of daily routine and disruptions to regularly scheduled activities ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%